2019
DOI: 10.1093/ehjci/jez155
|View full text |Cite
|
Sign up to set email alerts
|

The impact of plaque type on strut embedment/protrusion and shear stress distribution in bioresorbable scaffold

Abstract: Scaffold design and plaque characteristics influence implantation outcomes and local flow dynamics in treated coronary segments. Our aim is to assess the impact of strut embedment/protrusion of bioresorbable scaffold on local shear stress distribution in different atherosclerotic plaque types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…EROSION Study (Effective Anti-Thrombotic Therapy Without Stenting: Intravascular Optical Coherence Tomography-Based Management in Plaque Erosion) [47] was the first study to suggest that patient with acute coronary syndrome due to plaque erosion can be managed by effective antiplatelet therapy without stent implantation. Torii et al reported the impact of plaque type on stent strut [48]. However, high price and technical safety concerns restrict the application of OCT to a selected population of AMI, surrogates for predicting culprit lesions are needed in clinical practice.…”
Section: A/c As a Predictor For Plaque Vulnerability Inmentioning
confidence: 99%
“…EROSION Study (Effective Anti-Thrombotic Therapy Without Stenting: Intravascular Optical Coherence Tomography-Based Management in Plaque Erosion) [47] was the first study to suggest that patient with acute coronary syndrome due to plaque erosion can be managed by effective antiplatelet therapy without stent implantation. Torii et al reported the impact of plaque type on stent strut [48]. However, high price and technical safety concerns restrict the application of OCT to a selected population of AMI, surrogates for predicting culprit lesions are needed in clinical practice.…”
Section: A/c As a Predictor For Plaque Vulnerability Inmentioning
confidence: 99%
“…On the other hand, in acute coronary syndromes -a population that was underrepresented in the first stent studies -the calcific burden in culprit lesions is higher in males 11 . Plaque composition, especially an increased calcific burden, is a well-known predictor of TLR in metallic stents 12 and is expected also to have prognostic implications in Absorb BVS, as the acute gain is smaller following implantation of this device 13 that also has thicker struts which, in case of a fibrotic or calcific plaque, tend to protrude into the lumen, causing flow disturbances and a higher shear rate that predisposes to platelet activation and thrombus formation 14 . The differences in plaque composition between male and female patients may explain the numerically lower scaffold thrombosis rate noted in female patients in this study but also in the AIDA study in which 53.6% of the recruited patients were admitted with an acute coronary syndrome (Figure 1) 15 .…”
Section: Article See Page 615mentioning
confidence: 99%
“…There are several factors that can potentially influence endothelium recovery post stenting, including stent deployment depth, the scale of endothelial denudation, hemodynamic changes, and the structure and material properties of the stent (Kakinoki et al, 2018;Wang et al, 2018;Torii et al, 2020). Due to differences in individual vessel diameter and atherosclerotic plaque type, stent placement causes endothelium injury of various depths and scales (O'Brien et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of stent markedly alters vascular mechanics, especially blood flow patterns and fluid shear stress (FSS) (Gijsen et al, 2019;Torii et al, 2020). Under physiological conditions, endothelial cells are exposed to laminar FSS ranging from 10 to 20 dyn/cm 2 (Kwak et al, 2014).…”
Section: Introductionmentioning
confidence: 99%